1974
DOI: 10.1002/art.1780170303
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriolytic and bactericidal activity of sera and synovial fluids in rheumatoid arthritis and in osteoarthritis

Abstract: Bacteriolytic and bactericidal activity was evaluated in sera and synovial fluids of 28 patients with rheumatoid arthritis and 13 patients with osteoarthritis. An attempt was made to correlate the results with the concentrations of the total hemolytic complement, lysozyme, immunoglobulins, transferrin, and the titer of the Latex fixation. Bacteriolytic activity in all but 5 hypocomplementemic rheumatoid sera and in all osteoarthritic sera was normal. There was a correlation (P = 0.01) between bacteriolytic act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…11 Recent studies have suggested synovial fluid also may contribute to a joint's innate defense against certain microbial infections, primarily those caused by gram-negative organisms. 6,15 However, the specific immunologic properties and protective mechanisms of synovial fluid against common gram-positive bacterial pathogens that are encountered clinically remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…11 Recent studies have suggested synovial fluid also may contribute to a joint's innate defense against certain microbial infections, primarily those caused by gram-negative organisms. 6,15 However, the specific immunologic properties and protective mechanisms of synovial fluid against common gram-positive bacterial pathogens that are encountered clinically remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative prophylactic antibiotics include fusidic acid, cloxacillin (11), cefixime (12), vancomycin, and gentamicin (13). Interestingly, synovial fluid has been suggested to possess antibacterial properties (14)(15)(16) that are attributed to hyaluronic acid within the synovial fluid (17), the induction of bactericidal/permeability-increasing protein (15), or unknown compounds, including antimicrobial peptides, within the synovial fluid (14). We recently reported that this ostensible decrease in bacterial numbers, which is perceived to be an "antibacterial" effect, is actually due to the clumping of bacteria within synovial fluid, which masks the true microbial load levels (18).…”
mentioning
confidence: 99%
“…With regularity serum activities correlate positively with the severity of the disease. Elevated serum levels can also be observed in chronic rheumatoid arthritis [76,77], multiple injuries [74,78,79], postoperative states [80], and in neoplastic diseases [81]. Locally increased enzyme activities can be found in inflamed tissues, in inflammatory exudates, and in malignant tumours [82–86].…”
Section: Secretory Phospholipase A2 Group Iiamentioning
confidence: 99%